2018
DOI: 10.1002/advs.201800948
|View full text |Cite
|
Sign up to set email alerts
|

3D Cellular Architecture Affects MicroRNA and Protein Cargo of Extracellular Vesicles

Abstract: The success of malignant tumors is conditioned by the intercellular communication between tumor cells and their microenvironment, with extracellular vesicles (EVs) acting as main mediators. While the value of 3D conditions to study tumor cells is well established, the impact of cellular architecture on EV content and function is not investigated yet. Here, a recently developed 3D cell culture microwell array is adapted for EV production and a comprehensive comparative analysis of biochemical features, RNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
118
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 88 publications
14
118
1
Order By: Relevance
“…However, their parent cells cultured between 2D and 3D systems exhibited similar miRNA expression profile. Rocha, et al 56 also observed that striking differences between small RNAs detected in EVs and in donor cells, which support our results and other research reports indicating a specific sorting process of small RNAs into EVs 26,27 . As anticipated, replicates (2D-cell miRNAs and 3Dcell miRNAs) were clustered together.…”
Section: The 3d Cell Culture Derived Ev Rna Profile Shows a Significasupporting
confidence: 93%
See 3 more Smart Citations
“…However, their parent cells cultured between 2D and 3D systems exhibited similar miRNA expression profile. Rocha, et al 56 also observed that striking differences between small RNAs detected in EVs and in donor cells, which support our results and other research reports indicating a specific sorting process of small RNAs into EVs 26,27 . As anticipated, replicates (2D-cell miRNAs and 3Dcell miRNAs) were clustered together.…”
Section: The 3d Cell Culture Derived Ev Rna Profile Shows a Significasupporting
confidence: 93%
“…The harvested EVs showed typical round, cup shape via SEM imaging in both 2D and 3D culture conditions (Figure 2 B and D), while 3D culture-derived EVs showed the more dense distribution of smaller size. These observations were in agreement with Rocha, et al that exosomes released by tissue-engineered tumors were smaller than exosomes released by the same cells cultured in monolayer, and the 3D system is more active for producing exosomes 56,57 . It is interesting that our observation is the same as Rocha, et al report that the maximum period for conditioned media collection was 48 h for 2D.…”
Section: Ev Secretion Dynamics From 3d Cultured Cells Significantly Dsupporting
confidence: 92%
See 2 more Smart Citations
“…Some studies have reported that exosome produced by 3D cultures (Exos/EVs-3D) has more advantages than exosome produced by 2D cultures (Exos/EVs-2D) [50][51][52][53][54][55][56][57] in terms of the size, content, function and production efficiency of exosomes. The functions of exosomes differ according to their content, while Exos/EVs-3D contain a different profile of proteins and genetic materials compared to Exos/EVs-2D [52] .…”
Section: Culture For Exosome Generationmentioning
confidence: 99%